Influence of the Yucatan earthquake event - Li, Changcheng (Frontiers in Earth Science, 2023)
In recent years, seismic wave effects caused by meteorite impacts have been widely observed. The meteorite impact event that occurred 66 million years ago is one of the most famous impact events in Earth's history. The influences of the seismic wave field generated by this collision event on the solid Earth itself is worth exploring. Therefore, this study initially estimated the seismic source parameter information based on the multiring structure of the meteorite crater, and then simulates the seismic event. The results of this study provide a possible explanation for the formation of the Earth's tectonic plates. The findings of this study suggest that the seismic wave field generated by the meteorite impact event 65 million years ago may have caused the destruction of the Solid Earth, leading to the formation of the boundary between the Indian Ocean and the Pacific Plate. Simultaneously, this study has important significance for inspiring the development of new geoscientific methods.